Policy scenarios for a transition to a more resource efficient and circular economy - Bibas, Ruben (OECD Publishing, 2021)
Global materials use is expected to grow in the coming decades in the absence of new policies, bearing substantial negative impacts for the environment. This report analyses the mechanisms through which resource efficiency and circular economy policies can achieve a decoupling between economic growth and material use. Using the OECD's ENV-Linkages model, the report examines the economic and environmental impacts of a global material fiscal reform, which implements taxes on primary metal and mineral resources, and uses the revenue of these taxes to finance subsidies to recycled goods and to secondary metal production
Keywords: Environment